Impact of physical training mesocycle on athletic and specific fitness of elite boxers - Cepulenas, A.; Bruzas, V.; Mockus, P.; Subacius, V. (Archives of Budo, 2011)
Background and Study Aim. The indices of boxers` athletic and special fitness are important structural components of sports fitness as they influence the acquisition of the sports form. Thus, it is relevant to study the changes in the indices of boxers` athletic fitness, special physical fitness and working capacity after the physical training mesocycle. Materials and methods. The research participants were 10 elite boxers, candidates to the Lithuanian national boxing team, participants and prize winners at the Lithuanian boxing championships. Their mean age was 22.50±3.38 years. The physical training mesocycle lasted for four weeks in the preparation period. Special physical fitness and specific working capacity of boxers were tested using special diagnostic equipment "Kiktest-100" which consists of a standard boxing bag with a special device inside - dynamometer and a sensing element registering the impulses of blows; computer block registering the force of blows (kg), the number of blows, intervals between the blows, summative force of blows (kg) in a unit of time, and energy outlay (J). Results. After the physical training mesocycle the indices of boxers` explosive strength, speed strength and quickness improved. The single blow force to the boxing bag improved as well. After the physical training mesocycle, the force of single blows of boxers with their main and front hand and the force of the straight blow with their main hand improved to 253.37 ± 31.09 kg, the side blow - to 297.00 ± 45.07 kg, and the low blow - to 303.62 ± 42.18 kg. The average single blow power hitting the boxing bag 3 x 3 min increased from 76.72 ± 29.71 kg to 82.54 ± 33.41 kg. Conclusions. Four-week physical training mesocycle, consisting of 40 % of athletic training and 60 % of special physical training, had a positive effect on the changes in indices of boxers` athletic fitness. There was an improvement observed in the indices of boxers` athletic fitness performing explosive strength, speed strength and speed exercises. The force of blows hitting the boxing bag with the main and front hand increased as well. There was an increase in the indices of special anaerobic alactatic working capacity: number of blows, summative force of blows, and energy outlay hitting the boxing bag for 3 s, 5 s, and 8 s.